Students’ Ability To Use Descriptive Adjective In Sentence - Hendri Hendri (Anterior Jurnal, 2014)
This thesis deals with the use of the descriptive adjective in sentences. The objectives of this research are to find out the students‟ ability to use a descriptive adjective in sentences and describe the student's difficulties in using a descriptive adjective in sentences. The technique used in this research was descriptive quantitative. This research took the second year (XI) of MAN Tanjung Morawa. There are three classes for XI students that consist of 102 students in which class XI IPA1 = 30 students, XI IPA2 = 36 students, and XI IPS = 36 students. Since the researcher took 20%, so only 20 students were taken as the sample. The findings of this research concluded that for 20 students, there were 9 students or 45% were categorized as able. For 20 students, there were 11 students or 55% were categorized as unable. The result of the validity of the test is 0.67. It means that the test is "high to validity". The value of standard reliability above, then the result of the reliability of the test is 0.80. It means that the test is “good”. The test item number 7 was the most difficult one in which only 2 students were able in using descriptive adjective correctly. The test item number 7 related to the Compound Adjective.